IDENTIFIKASI POTENSI EKONOMI KECAMATAN TANJUNGSARI KABUPATEN GUNUNGKIDUL YOGYAKARTA - Hartarto, Romi Bhakti (Jurnal Ekonomi & Studi Pembangunan, 2016)
The intention of regional government of Special Region of Yogyakarta to make south area as the front page of regional economic development has been initiated. As one subdistrict located in the south area of Gunungkidul regency, Tanjungsari subdistrict has several prospects on economy, tourism, and resources due to its strategic and direct position near the Hindia Ocean and Southern Traffic Lane. This study aims to mapping economic potential based upon leading sectors as identified by Location Quotient (LQ) method and Klassen typology which is employed to characterize the economic pattern and structure. Based on LQ analysis, both manufacturing and construction sectors are the leading sectors which need to develop in advance since they are the supporting sectors nowadays and in the future. Meanwhile, there exists a shift in economic pattern from developing region to underdeveloped region according to Klassen typology.